THE BLAME GAME : MECHANISTIC CONCEPTIONS OF TEACHER EDUCATION AND ITS IMPACT ON SCHOOLING - Isaacs, Tracey; Waghid, Yusef (South African Journal of Higher Education, 2016)
With all the post-democracy policy directives and reform initiatives, education in South Africa is seemingly mechanistic and carrying prodigious productive logic: to produce students, to advance economic development, and so on. The active language of official educational policies is riddled with words such as ’assessment’, ’efficient’, ’high skills’ and ’progression’ that speak to a technical rationality bent on turning everything into ’science’ to obscure the general meaning. In this way the process of education is comparable to a sophisticated, intellectual machine - the more complex the machine becomes, the less control and understanding the teachers have over it (Braverman 1974). In this article, the authors consider the ways in which classroom and university teachers have been brutalised through bureaucratic processes and an allegiance to technical rationality, even while they imagine hermeneutic rationality and emancipatory rationality as radical alternatives to recovering the subject in a bureaucratic tangle of educational control.